Study on the Ground Movement in an Open-Pit Mine in the Case of Combined Surface and Underground Mining. (9th June 2020) - Wang, Zhenwei; Song, Gaofeng; Ding, Kuo
Abstract : The combined surface and underground mining method is typically used in an open-pit mine for better production and profits. However, the improved scale of mining operations at the combined mining conditions results in even more intensive strata movement and massive ground damages. This paper assesses the progressive development of the characteristics of roof movement with the longwall face advance and its influence on the ground movement at the slope area using physical models. The identification of strata zones at the combined mining conditions is also included. The results show the following: (1) the failure of the competent strong roof creates an inverse arch-shaped rock block structure, which compacts the loose rock fragments in the caved zone; (2) a bed separation occurs above the inverse structure at the top of the disturbed strata configuration and extends upward with the face advance until it approaches the continuous bending zone; (3) more intensive strata movement and ground damages are produced by the large-scale multiseam mining operations, while regular and more distinct strata zones in the disturbed configuration are identified for less intensive single-seam mining; and (4) the intensive and massive underground mining activities increase the slope strata movement at the surface mining side. This research suggests that a less intensive mining activity is preferred in the combined surface and underground mining conditions from the point of view of ground control.